The occurrence, acoustic characteristics, and significance of submerged reefs on the continental shelf edge and upper slope, northern South China Sea. (1st June 2015) - Li, Xishuang; Li, Xinzhong; Zhao, Qiang; Liu, Lejun; Zhou, Songwang
Abstract: Comprehensive research was performed to investigate the existence of submerged reefs on the continental shelf edge and upper slope outside the Pearl River estuary in the northern South China Sea to analyze the morphology and distribution of the coral reefs, identify their ages, and discuss their paleoenvironmental significance. The results show that the submerged reefs are distributed on the topographic high of the continental shelf and upper slope at a water depth of 140–420 m, with an outcropping area of over 700 km 2 . The submerged reefs are mainly topographically characterized by low mound protrusions, several to 20 m above the modern seafloor, and they exhibit three typical acoustic facies in the acoustic profile: punctate reflection, planar reflection, and mound reflection. Based on various geophysical data, we propose at least four stages (I–IV) of submerged reefs on the continental shelf edge and upper slope: The oldest stage I submerged reefs are covered by loose sedimentary strata of >100 m thickness, a minority of stage II submerged reefs outcrop on the modern seafloor, and most stage III and IV submerged reefs outcrop on the seafloor. The submerged reefs developed on the top of the sandy or muddy substrate on the continental shelf edge and upper slope and formed during a period of low sea level. Sea-level changes controlled periodic reef formation events, with stage I, II, and IV reef formation events corresponding to three low-sea-level events, i.e., at 1450, 600, and 20 ky B.P. Based on the maximum water depth (∼220 m) where the last glacial submerged reefs appeared, we estimate that the sea level during the last glacial maximum fell by ∼132–152 m. Further geophysical surveys and sampling need to be performed to clarify the actual distribution, type, and age of the submerged reefs in the study area. Highlights: We confirmed the existence of the submerged reefs on the outer edge of a wide shelf. We propose at least four stages (I¨CIV) of submerged reefs on the shelf edge. The study shows that sea-level changes controlled periodic reef formation events. The submerged reefs developed during a period of low sea level.